NUMERICAL INVESTIGATION OF GEOPOLYMER REINFORCED CONCRETE BEAMS UNDER FLEXURAL LOADING USING 3DNLFEA - Yosi Noviari Wibowo; Bambang Piscesa; Yuyun Tajunnisa (Institut Teknologi Sepuluh Nopember, 2022)
The development of geopolymer concrete is one of the most significant breakthroughs to replace the OPC concrete causing global warming issues. Investigations on the structural behavior of geopolymer concrete are limited and still need adjustments in numerical simulations to experimental results in previous studies. This study investigated the flexural behavior of geopolymer concrete as a structural member using the numerical method. The utilization of the finite element method is an alternative to widely determining the structural behavior of geopolymer concrete as a construction material. In this study, the author refers to the research conducted by Pham et al. The research developed a four-point bending test with variations in tensile steel reinforcement ratio. The results of the experimental tests that Pham has carried out will be verified by numerical simulation in three dimensions. The validation of experimental specimens with numerical specimens is done to compare the moment-curvature and the crack pattern of concrete. Numerical investigation accurately captures the structural behavior of moment-curvature and crack pattern of geopolymer concrete. The moment maximum deviation between experimental and numerical results is 1.3 to 2.4%. However, there are differences in the number and length of cracks in the bending moment area. The difference of crack pattern in the bending moment area between experimental results and numerical results due to the modeling did not consider the input of fracture energy. The experiment from referenced studies did not include fracture energy data, so the 3DNLFEA modeling used the fracture energy value of OPC concrete.